"All These Look to You": Reading Psalm 104 with Animals in the Anthropocene Epoch. (July 2019) - Stone, Ken
Psalm 104 is associated with biblical creation theology, but it seldom receives as much attention as the book of Genesis. Yet Genesis has been and continues to be used to justify human dominion over other animals, which has contributed to a new era in the earth's history known as the "Anthropocene" epoch. In contrast, Psalm 104 provides an ecological representation of creation that recognizes God's care for animals. Humans appear in the psalm, but only as one creature among others. A focus on Psalm 104 may foster an approach to biblical creation theology that is more attentive to animals and useful as an ecological frame for reading Genesis and other texts.